Sporozoite antibodies and malaria in children in a rural area of The Gambia. - Snow, R; Shenton, F; Lindsay, S; Greenwood, B; Bennett, S; Wheeler, J; Del Giudice, G; Verdini, A; Pessi, A (1989)
Sporozoite antibody levels were measured in a group of children aged one to nine years resident in a rural area of The Gambia, using an ELISA to the repeat peptide (NANP)40. The prevalence and titre of antibodies varied with age but not with sex or ethnic group. Significant variations in prevalence were recorded within a group of adjacent villages. Children who were seropositive at the beginning of the dry season had higher spleen and parasite rates both at this time and at the end of the subsequent rainy season than did seronegative children, suggesting that they were exposed more frequently to infection. However, seropositive children had fewer episodes of fever accompanied by high levels of parasitaemia than did seronegative children, suggesting that they had a greater degree of clinical immunity. No differences were found in seroprevalence rates or in mean antibody titres between children who slept under conventional or Permethrin treated bed nets and those who did not, even though bed nets significantly reduced the number of bites by vector mosquitoes.